p53 and p16 expression profiles in vulvar cancer: a translational analysis by the Arbeitsgemeinschaft Gynäkologische Onkologie Chemo and Radiotherapy in Epithelial Vulvar Cancer study group - Woelber, Linn; Prieske, Katharina; Eulenburg, Christine; Oliveira-Ferrer, Leticia; de Gregorio, Nikolaus; Klapdor, Ruediger; Kalder, Matthias; Braicu, Iona; Fuerst, Sophie; Klar, Maximilian; Strauss, Hans Georg; Beckmann, Matthias; et al. (American Journal of Obstetrics and Gynecology, 2021)
Background: There are 2 known pathways for tumorigenesis of vulvar squamous cell carcinoma—a human papillomavirus–dependent pathway characterized by p16 overexpression and a human papillomavirus–independent pathway linked to lichen sclerosus, characterized by TP53 mutation. A correlation of human papillomavirus dependency with a favorable prognosis has been proposed. Objective: The objective of the study was to further understand the role of human papillomavirus and p53 status in vulvar squamous cell carcinoma and characterize its clinical relevance. Study Design: The Arbeitsgemeinschaft Gynaecological Oncology Chemo and Radiotherapy in Epithelial Vulvar Cancer-1 study is a retrospective cohort study of 1618 patients with primary vulvar squamous cell carcinoma Fédération Internationale de Gynécologie et d'Obstétrique stage ≥1B treated at 29 gynecologic cancer centers in Germany between 1998 and 2008. For this translational substudy, formalin-fixed paraffin-embedded tissue was collected. A tissue microarray was constructed (n=652 samples); p16 and p53 expression was determined by immunohistochemistry. Human papillomavirus status and subtype were analyzed by polymerase chain reaction. Results: p16 immunohistochemistry was positive in 166 of 550 tumors (30.2%); p53 staining in 187 of 597 tumors (31.3%). Only tumors with available information regarding p16 and p53 immunohistochemistry and without p53 silent expression pattern were further analyzed (n=411); 3 groups were defined: p53+ (n=163), p16+/p53− (n=132), and p16−/p53− (n=116). Human papillomavirus DNA was detected in 85.6% of p16+/p53− tumors; human papillomavirus-16 was the most common subtype (86.3%). Patients with p16+ tumors were younger (64 vs 72 years for p53+, respectively, 69 years for p16−/p53− tumors; P<.0001) and showed lower rates of lymph-node involvement (28.0% vs 42.3% for p53+, respectively, 30.2% for p16−/p53− tumors; P=.050). Notably, 2-year-disease-free and overall survival rates were significantly different among the groups: disease-free survival, 47.1% (p53+), 60.2% (p16−/p53−), and 63.9% (p16+/p53−) (P<.001); overall survival, 70.4% (p53+), 75.4% (p16−/p53−), and 82.5% (p16+/p53−) (P=.002). In multivariate analysis, the p16+/p53− phenotype showed a consistently improved prognosis compared with the other groups (hazard ratio, 0.66; 95% confidence interval, 0.44–0.99; P=.042). Conclusion: p16 overexpression is associated with an improved prognosis whereas p53 positivity is linked to an adverse outcome. Our data support the hypothesis of a clinically relevant third subgroup of vulvar squamous cell carcinoma with a p53−/p16− phenotype showing an intermediate prognosis that needs to be further characterized.
CRIS-Team Scopus Importer:2021-04-09
Keywords: HPV; p16; p53; prognosis; vulvar cancer